(untitled) (Ocean and Coastal Research, 2024)
Some fish species can be used as target species and bioindicators of environmental disturbances. In this context,biological indicators such as the length, weight, and height of lapillus otoliths of the ariid species Cathorops spixiiand Genidens genidens were considered bioindicators of contamination of the Cananéia-Iguape estuarinelagoon complex (CIELC) in this study. The CIELC is an estuary with spatial and temporal differences regarding itshydrobiochemical properties and this characteristic has been related to changes in biological predictors such as theotolith morphometrics of estuarine fish. Therefore, this study aimed to verify the responses of otolith dimensions tosexual and temporal changes, throughout the CIELC. In total, 163 wild catfish C. spixii and 55 G. genidens werecollected during the winter period of 2009, 2017, and 2018 in the CIELC. In general, the weight and length of lapillusotoliths of C. spixii and G. genidens were good metrics adjusted to fish growth. Females of C. spixii were significantlylarger than males and subadults and there were no significant differences regarding the sexual approach of G.genidens. The temporal approach showed significant differences between the years for both catfish. C. spixii sampledin 2009 and 2018 showed greater total length (TL) and total weight (TW) when compared with fish from 2014 and2017 (p < 0.05). G. genidens collected in 2018 had greater TL and TW than the specimens sampled in the otheryears (p < 0.05). Otolith dimensions seem to have followed this same pattern, since females of C. spixii had highervalues for otolith weight, height, and length than males and subadults (p < 0.05). The data obtained in this study canbe a potential tool for application combined with other ecological analyses and conservation studies in the CIELC.